The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/nano12101740
|View full text |Cite
|
Sign up to set email alerts
|

Static and Free Vibration Analyses of Single-Walled Carbon Nanotube (SWCNT)–Substrate Medium Systems

Abstract: This paper proposes a novel nanobar–substrate medium model for static and free vibration analyses of single-walled carbon nanotube (SWCNT) systems embedded in the elastic substrate medium. The modified strain-gradient elasticity theory is utilized to account for the material small-scale effect, while the Gurtin–Murdoch surface theory is employed to represent the surface energy effect. The Winkler foundation model is assigned to consider the interactive mechanism between the nanobar and its surrounding substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…To this aim, this section gives a detailed description of the analysis of racquet [26]. The analysis was carried out by applying Euler-Bernoulli's theory, thus deriving the necessary formulations as the dimensions of the racquet meet the criterion of thin column theory [27,28]. In the analytical case, a model was characterized by a partial differential equation with respect to position and time coordinates.…”
Section: Analysis Of Natural Frequencymentioning
confidence: 99%
“…To this aim, this section gives a detailed description of the analysis of racquet [26]. The analysis was carried out by applying Euler-Bernoulli's theory, thus deriving the necessary formulations as the dimensions of the racquet meet the criterion of thin column theory [27,28]. In the analytical case, a model was characterized by a partial differential equation with respect to position and time coordinates.…”
Section: Analysis Of Natural Frequencymentioning
confidence: 99%
“…This hindrance is particularly noticeable when dealing with single-walled carbon nanotubes (SWNTs), which are expected to show nontrivial correlation between mechanical deformation and their physical properties [ 9 , 10 ]. This may be a reason why tremendous efforts based on numerical simulations [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ] and continuum approximation theory [ 11 , 17 , 19 , 20 , 21 , 22 ] have been exerted in exploring the buckling behavior of SWNTs under loading. Several theoretical studies have revealed that axial buckling of SWNTs is highly dependent on the lattice irregularity [ 23 , 24 ] and tube chirality [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…In that research, a finite difference method was applied in the case of column having a rectangular cross-section or an I-shaped cross-section whose dimensions were variable along the axis of the column in order to compute the critical buckling load. On the other hand, in nanomechanics, there are specific methods to analyze the buckling of nanobeams resting on elastic substrate media [ 12 ].…”
Section: Introductionmentioning
confidence: 99%